Isotopic characterization of vanillin ex glucose by GC-IRMS: New challenge for natural vanilla flavour authentication? - Wilde, Amelie S.; Frandsen, Henrik Lauritz; Greule, Markus (Food control, 2019)
Vanilla flavour is highly vulnerable to economically motivated adulteration as the main component vanillin can be derived by much cheaper production methods than by the extraction from vanilla pods. The δ13C ranges for synthetic vanillin from petroleum and C3 plants are depleted in comparison to the reported δ13C range for vanillin from vanilla orchids. However, with the invention of new biosynthetic pathways, vanillin overlapping with the characteristic δ13C range reported for vanillin from vanilla pods can be produced. Here, we present bulk and site-specific analysis by GC-IRMS of stable carbon and hydrogen isotope ratios of vanillin derived from glucose. This is the first time a δ13C value for biovanillin that is higher compared to vanillin from vanilla pods is reported. The possibility to simulate the δ13C range of vanillin from vanilla pods by combining vanillin derived from inexpensive sources constitutes an increased risk for fraud being perpetrated while remaining unnoticed.